Bioassay evaluation of residual activity of attractive toxic sugar-treated barrier fence in the control of Phlebotomus papatasi (Diptera: Psychodidae) - Abedin Saghafipour; Hassan Vatandoost; Ali Reza Zahraei-Ramazani; Mohammad Reza Yaghoobi-Ershadi; Yavar Rassi; Mohammad Reza Shirzadi; Amir Ahmad Akhavan (Journal of Vector Borne Diseases, 2016)
Background & objectives: Phlebotomus papatasi is the main vector of the zoonotic cutaneous leishmaniasis (ZCL) in Qom Province and many other provinces of Iran. Attractive toxic sugar baits (ATSB) treated barrier fence is one of the new methods for controlling the vectors such as sandflies. The present study was designed to evaluate the residual activity of ATSB-treated barrier fence that was used in control of P. papatasi. Methods: Following the selection of villages in Markazi district of Qom Province, central Iran during 2015 for ATSB and ASB (bait containing no active ingredient) methods; barrier fences on the ground in front of the rodent′s colony were installed. A total of four conical tubes were installed and fixed on surfaces of treated barrier net of dimension 25 Χ 25 cm at biweekly interval. In each conical tube, 10 sand flies were released and after 3 min of exposure they were transferred to sterile cups. After 24 h, the obtained results were recorded according to the survival and mortality rate of sandflies. These tests were carried out five days after the installation of barrier fences, and repeated every 15 days until the mortality rate decreased to 60-65%. Results: The bioassay tests results showed that the mortality rate of P. papatasi on ATSB-treated barrier fence for 5, 15, 30 and 45 days after spraying was 100, 95.83, 88.18 and 66.67% respectively, which decreased to 50.83% after 60 days. Interpretation & conclusion: Persistence and residual activity of the active ingredient of the bait in the hot and dry climatic conditions of Qom Province remained significantly effective for at most 45 days, which subsequently decreased at a high rate. Hence, every 45 days barrier fences need to be impregnated with ATSB bait. The method also appeared cost-effective and could be practical in implementation of vector control programmes against ZCL.